MODERN MIRACLES: NAVIGATING THE ETHICAL AND LEGAL LABYRINTH OF ASSISTED REPRODUCTIVE TECHNOLOGIES. - Dr. Anju Choudhary; Rupali Mehta (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This research paper examines the existing legal framework governing Assisted Human Reproduction Technologies (ART). This research demonstrates that the existing legal framework is insufficiently prepared to address the novel legal, ethical, and social challenges that arise from the utilization of assisted reproductive technology as a pathway to parenthood. This study reveals that while ART aims to assist childless individuals and couples in achieving parenthood, its intricate nature and the lack of comprehensive legal frameworks result in the exploitation of women, including surrogates, egg donors, and commissioning mothers, by the so-called ’Fertility Clinics’ involved in the process. A comprehensive legislative framework is urgently required to address the legal complexities arising from the utilization and potential misuse of Assisted Reproductive Technologies as a pathway to parenthood.